Rapid neuralized and vascularized osteogenesis in infected bone defect using biomimetic biomineralized and antibacterial hydrogels - Deng, Yuhao; Chen, Song; Tuerxun, Maimaitiaili; Xiong, Xuekang; Tang, Jianfei (Frontiers in Bioengineering and Biotechnology, 2025)
Infected bone defects represent one of the most prevalent clinical conditions, affecting millions of patients annually. The local infection and necrosis associated with these defects exacerbate the injury, prolong healing times, and result in significant localized pain, presenting a substantial challenge for clinical repair. In this study, we developed a biomimetic mineralized and antibacterial imCOL1MA hydrogel by employing methacrylated COL1, composite native bone inorganic salts (CNBIS), and Magainin II-PLGA microspheres (mMicrospheres), which was further loaded with bone marrow stem cells (BMSCs) to form osteogenic engineered bone for infected bone defects repair. Briefly, we first optimized the concentration of COL1MA for BMSCs survival, then adjusted proportion of CNBIS to create an appropriate osteoinductive microenvironment, and encapsulated Magainin II in poly (lactic-co-glycolic acid) (PLGA) microsphere for long-term antimicrobial function. Consequently, the promising mineralized and antibacterial imCOL1MA was prepared using 10% COL1MA, 2% CNBIS, and 1% mMicrospheres. The imCOL1MA scaffold served as significant antimicrobial efficacy, excellent biodegradability, good biocompatibility, and osteoinductive microenvironment. As a result, the engineered bone could achieve rapid (only 4 weeks) vascularized and neuralized bone regeneration in a rabbit model of infected bone defects.